Pengaruh Perlakuan Alkalisasi KOH dan Variasi Waktu Perendaman terhadap Sifat Mekanik Komposit Serat Luffa Cylindrica - Lucky Akbar Pangestu; Deni Andriyansyah (Pusat riset dan Inovasi Nasional, 2025)
This study aims to investigate how variations in the soaking time of Luffa cylindrica fibers in alkaline solutions affect the mechanical properties and fire resistance of the resulting composite material. The use of natural fibers is an important step in finding environmentally friendly and sustainable alternatives to replace synthetic materials. Luffa cylindrica fibers were chosen for their advantages, such as being lightweight, strong, and abundantly available. However, natural fibers like luffa contain non-cellulose compounds, such as lignin and hemicellulose, that can hinder strong bonding with the resin matrix. Therefore, pre-treatment with an alkaline solution is necessary to remove these interfering substances. In this study, composites were made using the hand lay-up method with polyester resin as the main matrix. The treatment variable tested was the fiber soaking time in KOH solution, with three variations: 2 hours, 4 hours, and 6 hours. After the composite fabrication, the samples were tested through several standard tests, including tensile tests to measure the material's strength under tension, impact tests to assess toughness, and burn rate tests to evaluate fire resistance. Additionally, macro and micro photo analysis (using SEM if possible) will be conducted to observe fracture characteristics and the quality of the fiber-resin bond. The expected outcome is that longer alkaline soaking will significantly improve tensile strength and toughness. Furthermore, longer soaking is also expected to improve fire resistance by forming a char layer, which acts as a thermal insulator, slowing heat transfer and reducing the rate of pyrolysis.